2021
DOI: 10.1093/humupd/dmab017
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyosis pathogenesis: insights from next-generation sequencing

Abstract: BACKGROUND Adenomyosis, characterized by the presence of islands of endometrial tissue surrounded by hypertrophic smooth muscle cells within the myometrium, is one of the most challenging uterine disorders in terms of diagnosis and management. Adenomyosis presents with pelvic pain, excessive uterine bleeding, anemia and infertility. The relative contributions of abnormal endometrial tissue and myometrial smooth muscle cells to the development and growth of adenomyosis are not well understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 67 publications
1
77
0
Order By: Relevance
“…Interestingly, in endometriotic lesion, Suda and collegues [99] described higher mutant allele frequency (MAF) of mutations on cancer-associated genes compared to normal endometrial epithelium. This finding suggests that endometrial cells harboring cancerassociated mutations, once reaching the ovarian surface by retrograde flow, may present selective advantages at this ectopic site, leading to the development of endometriotic lesion with an amplification of the clone [99,103]. The findings reinforce John Sampson's century-old retrograde hypothesis of the origin of endometriosis at genomic level [11].…”
Section: Molecular Aspects In the Pathogenesis Of Endometriosis And Adenomyosissupporting
confidence: 65%
See 3 more Smart Citations
“…Interestingly, in endometriotic lesion, Suda and collegues [99] described higher mutant allele frequency (MAF) of mutations on cancer-associated genes compared to normal endometrial epithelium. This finding suggests that endometrial cells harboring cancerassociated mutations, once reaching the ovarian surface by retrograde flow, may present selective advantages at this ectopic site, leading to the development of endometriotic lesion with an amplification of the clone [99,103]. The findings reinforce John Sampson's century-old retrograde hypothesis of the origin of endometriosis at genomic level [11].…”
Section: Molecular Aspects In the Pathogenesis Of Endometriosis And Adenomyosissupporting
confidence: 65%
“…Moreover, targeted deep sequencing analyses of epithelial cells demonstrated recurring KRAS mutations in both adenomyosis and eutopic basalis endometrial glands [99,101]. This finding suggests that adenomyosis originates from the basalis portion of endometrial glands, harboring KRAS mutation, supporting the Cullen's invagination theory [7,8,103].…”
Section: Molecular Aspects In the Pathogenesis Of Endometriosis And Adenomyosismentioning
confidence: 67%
See 2 more Smart Citations
“…In a study within situ hybridization and immunohistochemistry, it was found that the endometrial glands in adenomyosis selectively express more human chorionic gonadotropin (hCG) receptor mRNA and immunoreactive receptor protein, compared to the present [31][32][33][34]. It seems that ΗCG/LH receptor expression levels do not differ at different sites of the normal endometrium, but increased expression of this receptor may give epithelial cells the ability to invade the myometrium and form adenomyotic islets.…”
Section: Pathogenesismentioning
confidence: 99%